Kesalahan Penulisan Arab Melayu Pada Buku Pengayaan Materi Ajar Pendidikan Budaya Melayu Riau Edisi 2019 Kelas V Sekolah Dasar - Isni Juniyati; Anisa Enjelina; Novia Oktari Yulanda; Hasnah Faizah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The research aims to analyze and describe errors in writing Malay Arabic script, especially in the 2019 edition of the 2019 edition of the book, Enrichment of Riau Malay Culture Teaching Materials for class V of Elementary Schools, with the aim of improving and becoming a guide for correct writing of Malay Arabic script. The limited availability of teaching materials will not be separated from errors. and shortcomings in its presentation. The method used in this research is a qualitative descriptive method using observation techniques and literature study in data collection which was carried out on November 7 2023 by analyzing books. This research resulted in several errors in writing akasara in the 2019 edition of the 2019 edition of the Belayu Riau Culture enrichment teaching material book for class V of elementary schools and showed and explained the correct writing based on the Malay Arabic book guidelines.